Z Boson Production via p-p and Pb-Pb Collisions at spp=5.02 TeV. (24th September 2020) - Kisslinger, Leonard S.; Das, Debasish
Abstract : We estimate the production of Z a bosons, with a as the component of a Z vector boson, via p -p collisions using previous work on J / Ψ, Ψ 2 S production in p -p collisions, with the new aspect being the creation of Z a bosons via quark interactions. We then estimate the production of Z a bosons via Pb-Pb collisions using modification factors from previous publications.